A numerical study of coupled non-linear equations of thermo-viscous fluid flow in cylindrical geometry - Pothanna, N.; Aparna, Podila; Gorla, Rama Subba Reddy (Zielona Góra: Uniwersytet Zielonogórski)
In this paper we present numerical solutions to coupled non-linear governing equations of thermo-viscous fluid flow in cylindrical geometry using MATHEMATICA software solver. The numerical results are presented in terms of velocity, temperature and pressure distribution for various values of the material parameters such as the thermo-mechanical stress coefficient, thermal conductivity coefficient, Reiner Rivlin cross viscosity coefficient and the Prandtl number in the form of tables and graphs.
Keywords: Reiner Rivlin Cross viscosity; thermal conductivity; thermo-stress viscosity; Prandtl number